Over a million students use our free study notes to help them with their homework
6x + 2y = -3 (1)*3 4x - 3y = 11 (2)*2 18x + 6y = -9 (1) 8x - 6y = 22 (2) (1) + (2) = 18x +8x + 6y - 6y = -9 + 22 => 26x = 13 => x = 1/2 sub x into (1) => (6 * 0.5) + 2y = -3 3 + ...
When performing live calculations of examples of questions for the students, I shall begin by writing down an approach to how they should tackle the problem. This will only take a minute and I’ve found do...
This is a very common type of question that might be asked in an exam and there are 3 methods we could use to solve this; by substitution, by elimination (or subtraction) or by using straight line graphs....
BIDMAS
Following BIDMAS, multiply the bracket out before the addition of the 2y.
3y(5y+3) = 15y2+9y
adding the 2y gives the calculation of 15y2 + 9y +2y = 15y<...
In order to solve this equation we need to find a common denominator for the 2 fractions. It is impossible to name the common denominator while working with unknown variables such as x,y etc. but we know ...
←
634
635
636
637
638
→
Internet Safety
Payment Security
Cyber
Essentials